REFLECTIONS OF NATIONAL AND CULTURAL ACTIVITIES BY MARTYNAS JANKUS AND OTHER PRUSSIAN LITHUANIA PEOPLE IN THE PUBLICATIONS OF NEWSPAPER “VARPAS” (1889–1905) - POCYTĖ, SILVA (Knygotyra, 2015)
“Varpas” is the newspaper, published in the years 1889–1905 in the Prussian Lithuania (Lithuania Minor). It was intended for people from the Lithuania Major belonging to the Tsarist Russia at that time, where the Lithuanian language press in Latin letters was prohibited by the Empire government in 1864–1904. The main goals of the article are: (a) to highlight the culture movement aspirations of Martynas Jankus as the most representative figure of Prussian Lithuanians (lietuvininkai), as well as other lietuvininkai culture movement members; (b) to analyse the most important national actualities in Prussian Lithuania at that time; and (c) to introduce the opinion about lietuvininkai way of living to the Lithuania Major people. All this is made on the basis of materials from the “Varpas” publications. Such analysis is possible because of the fact that we can find important Lithuanian culture figures such as Martynas Jankus, Morta Zauniūtė, Jurgis Lapinas, etc. among the “Varpas” editors. The problems of the Lithuanian culture situation in Prussian Lithuania were also pointed by outstanding Lithuania Major culture workers, such as Vincas Kudirka, Jonas Basanavičius, Jonas Šliūpas, etc.The theme is new and actual for the following reasons. In spite of rather wide research studies on the nationalist movement by Vincas Kudirka, reflected from “Varpas” social and national aspirations, our historians still didn’t pay actual attention to the same activities by Martynas Jankus in Lithuanian historiography. We can define some actual and predominant themes in “Varpas” publications: (a) local nationality situation and the problem of lietuvininkai denationalization; (b) the decreasing number of local Lithuanian-speaking people; (c) cultural and political activities of lietuvininkai; and (d) national collaboration and contacts between Lithuanians from Prussian Lithuania and Lithuania Major, including obstruction aspects here.The analysis of actual texts allowed us the following conclusion. Lithuanians in Lithuania Major understood the Lithuanian culture societies in Prussian Lithuania as an appropriate possibility to realize their own national and political aspirations. Anyway, the integration process of all people from both Lithuanias, separated historically by the Nemunas river at that time, was very problematic because of a different political, confessional and cultural situation in the period of the end of the 19th–beginning of 20th Centuries here. The ideas of joint Lithuanian culture movement were first pointed by the most active lietuvininkai culture figures, including Martynas Jankus. On the other hand, the main part of common lietuvininkai people were defined locally by a conservative understanding of their living area, determined by different political, cultural and economic life experience as compared with the situation in Lithuania Major.
Keywords: ...